2015
DOI: 10.7314/apjcp.2015.16.1.333
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and Practices Among Dentists and Senior Dental Students in Iran Toward Tobacco Cessation as an Effort to Prevent Oral Cancer

Abstract: Background: Oral health professionals are responsible in Iran for providing a brief tobacco cessation program to smoker patients. The aim of this study was to assess Iranian dental student and dentist practice, knowledge and attitudes toward smoking cessation programs. Materials and Methods: A valid and reliable self-administered questionnaire was designed and distributed to 150 dentists working in Isfahan-Iran and 60 dental students. Some questions were developed based on the expected 5A tobacco cessation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…46 The remaining 31 studies (81.6%) utilized author-created surveys or surveys based on items from previous studies. [21][22][23][24][25][26][27][28][29][30][31][32][33][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Of those 31 studies, ten (33.3%) reported pilot testing the measure. Nine (29%) reported conducting some psychometric testing of the measure (e.g., Cronbach's alpha, split-half reliability, testretest reliability, factor analysis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The remaining 31 studies (81.6%) utilized author-created surveys or surveys based on items from previous studies. [21][22][23][24][25][26][27][28][29][30][31][32][33][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Of those 31 studies, ten (33.3%) reported pilot testing the measure. Nine (29%) reported conducting some psychometric testing of the measure (e.g., Cronbach's alpha, split-half reliability, testretest reliability, factor analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Nine studies (23.7%) reported students' plans for future practice of tobacco cessation. 33,49,51,53,55,[62][63][64] Dentist role attitudes. Rates ranged from 54% of students willing to provide tobacco cessation 61 to 96% willing to use anti-tobacco programs in practice in order to advise patients to quit.…”
Section: Dental Student Practice Of Tobacco Cessationmentioning
confidence: 99%
“…Another instance of counseling that can be advantageous in the dental box is smoking cessation, not only for its impact on oral cancer, but because of its negative impact on overall health. Unfortunately, numerous recent studies have shown that dentists do not have the necessary skills to provide this type of counseling, which is usually of very poor quality 14,15 . While a direct reference to smoking cessation was not found in the curricula, it is important to note that there are guidelines established by the Chilean Ministry of Health to encourage dentists to provide counseling in this area 16 .…”
Section: Discussionmentioning
confidence: 99%
“…They include the lack of time, fear of the patient's reaction or resistance in accepting the approach, fear that the patient will lose trust in the professional, difficulty in addressing the topic, also being a smoker, lack of knowledge about the topic, lack of reimbursement, and fear of the reaction of colleagues [9,14,16,17,27,28,39,[41][42][43][46][47][48][49][50][51][52][53][54][55][56]. Once receiving training on tobacco cessation the graduation students and dental health professionals perceive significantly reduction on the pointed barriers [43].…”
Section: Barriers and Facilitators To Tobacco Use Cessation In Dentistrymentioning
confidence: 99%
“…Important aspects such awareness, attitude, practices, willingness and barriers were evaluated using hand-delivered, self-administered or via electronic contact were searched. Studies were conducted in many different clusters like dental universities [62], dental health professionals [7,9,12,13,17,32,46,48,[50][51][52]55,56,[63][64][65], dental insurance companies [61], students [1 5,21,28,31,32,38,39,45,47,49,51,53,55,66], dental patients who use tobacco [30,67,68] and dental teachers [44].…”
Section: Surveysmentioning
confidence: 99%